PERSPEKTIF KH. AHMAD DAHLAN TENTANG PENGEMBANGAN MASYARAKAT ISLAM - Elhany, Hemlan (P3M STAIN Jurai Siwo Metro, 2013)
Kyai Ahmad Dahlan is a scholar who works for a truth, not accept anything that is done by their ancestors. In this case, knowledge and expertise is necessary, as he try to respond to the existing tradition then compared to what it should be. It raises awareness of the truth questioned again about something that has been believed and executed on time. Kyai Ahmad Dahlan, the founder of Muhammadiyah always use guidelines verses the qurâan, because it is so intense he examines al qurâan and he was very diligent in translate al qurâan. Therefore, he always emphasized that al qurâan as a principal basis and foundation all activities of life. Community development perspective according to KH. Ahamad Dahlan explained the concept of everyday life by the qurâan guidelines.Â Â Â Keywords: Islamic Community Development, Social, Culture.